Consumer behavior on the market with food - Jana Turčínková; Jana Stávková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2006)
The paper deals with consumer behavior on the market with selected food products. It focuses on expenditures on food, development of prices and comparison of results among EU countries. When comparing the development of consumer prices and incomes in 1990–2003, it is obvious that the growth of income was lower then the total increase of consumer prices. There were not only changes in price levels, but also in the structure of consumer expenditures, where we can see growth of expenditures for housing and decline in share of expenditures for food. In the Czech Republic, there was a decrease in consumption of beef and pork meet, and increase in poultry consumption. The consumption of fish is significantly below the EU average. Consumption of butter, potatoes and sugar reaches the similar level as the EU average. The analysis of motives for changes in consumption of selected foodstuffs provides some insight in reasons for changes in consumption of bakery products and sweets, where it mostly is the healthy lifestyle (motive for whole-grain bakery product consumption) and improved market offer and advertising (for sweets and durable bakery products). Changes in meat consumption are motivated by healthy lifestyle for poultry and fish and improved market offer and advertising for canned meat products and salamis. Advertising and improved market offer played an important role for changes in consumption of yoghurts and cheeses, healthy lifestyle caused changes of yoghurts and milk. In category of selected beverages, it were advertising and improved market offer the motives for change of consumption of tea, wine and mineral waters, while healthy lifestyle motivated the change of mineral water consumption.